The effects of endurance training on muscle oxygen desaturation during incremental exercise tests: a systematic review and meta-analysis - Yogev, Assaf; Arnold, Jem I.; Nelson, Hannah; Rosenblat, Michael A.; Clarke, David C.; Guenette, Jordan A.; Sporer, Ben C.; Koehle, Michael S. (Frontiers in Sports and Active Living, 2024)
Minimum muscle oxygen saturation (SmO2min) measured via near-infrared spectroscopy (NIRS) is a common measure during incremental exercise testing (IET). Our objective was to determine the effects of pre-to-post endurance training on SmO2min (∆SmO2min) during an IET, using a meta-analysis.MEDLINE, EMBASE, and SPORTDiscus.Studies including healthy individuals had to meet the following criteria: (1) endurance training intervention; (2) peripheral muscle NIRS; (3) incremental exercise test pre/post training; (4) SmO2 or analogous saturation parameter measured.A PEDro scale was used for risk of bias analysis. A random effect meta-analysis model was used to synthesize the effect of training on ∆SmO2min in individual studies. Statistical heterogeneity was quantified using I 2 statistic. A meta-regression was used to estimate the effect of training on the relationship between peak cycling power output (Wpeak), peak pulmonary oxygen uptake (VȮ2peak), and ∆SmO2min. A mixed-effect model was used to estimate categorical variables.Five studies met the inclusion criteria. No difference in SmO2min was detected following training pre-and post-intervention IETs. A trend for an effect of training on the relationship between Wpeak and ∆SmO2min was observed (p = 0.06).This meta-analysis showed no effects of endurance training on SmO2min during an IET. Our results showed a trend for an effect of training on the relationship between Wpeak and ∆SmO2min, with no effect for VȮ2peak and ∆SmO2min. It is possible that SmO2min is not affected by endurance training, and may be used as a physiological marker for improvements in submaximal performance rather than at peak.